Manajemen Intraoperative Nausea and Vomiting (IONV) pada Pasien Seksio Sesarea dengan Anestesi Spinal - Apsari, Ratih Kumala Fajar; Jufan, Akhmad Yun; Sari, Dhanty Dwita (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Spinal anesthesia is the most commonly used anesthesia for caesarean section with it being safely, quickly and easy to administer. Current literature indicates a high incidence of intraoperative nausea and vomiting (IONV) during caesarean section under spinal anesthesia up to 80% likely to suffer from nausea and vomiting because of the pregnancy itself. This is applicable not only to the first 3 months of pregnancy but also to the last trimester due to the reduced tone of the esophagogastric junction and an increased intraabdominal pressure. During abdominal surgery under regional anesthesia, nausea may happen due to several contributing factors such as sympathetic blocks followed by parasympathetic dominance with hypotension which is the most important cause of nausea after spinal anesthesia, decreased perfusion of central nervous system, anxiety, and sudden abdominal movements during surgery